Music in Kenyan Christianity: Logooli Religious Song. Jean Ngoya Kidula. 2013. Bloomington: Indiana University Press. 17 bw illus., 53 music exs, index, 312pp. - Bethke, Andrew-John (International Library of African Music, 2014)
pages: 149-151
Keywords: Christianity; African Music; Kenya; Religious Song